Diaphragm Connections in Structures with Rocking Timber Walls. Issue 2 (1st May 2017) - Moroder, Daniel; Pampanin, Stefano; Palermo, Alessandro; Smith, Tobias; Sarti, Francesco; Buchanan, Andy
Abstract: Tall timber structures require lateral load-resisting elements which are very stiff and strong without complex connections. Post-tensioned timber (Pres-Lam) walls provide such properties and can also limit damage in case of extreme seismic events. Low damage can only be guaranteed if the connections between the walls and the diaphragm can transfer the horizontal loads and accommodate the displacement incompatibilities from the seismic rocking of the walls. This paper describes an experimental program on a post-tensioned timber wall specimen with ten different wall-to-diaphragm connections. The test results show that the degree of decoupling between rotational and translational deformations can significantly affect the strength and stiffness of the overall wall–beam system. A cost analysis showed that the higher the degree of decoupling, the more expensive the connection. If the wall-to-diaphragm interaction is not eliminated by decoupling at the connection, both the strength and stiffness of the wall–beam system are increased. The level of enhancement can be determined by an iterative procedure which is based on equilibrium equations and the stiffness of the floor beams and the connection.